The institutional image of the KPK on the dismissal of KPK employees who did not pass the national insight test (Fairclough's critical discourse analysis) - Vina Uctuvia; Malik Sofy; Abdul Hanan (IRecall Journal, 2025)
There was a phenomenon where the KPK Law rules were the consequence of the KPK Law modification where all KPK personnel from superiors to employees had to become ASN as of November 1, 2021, however, there were some abnormalities where KPK chairman Firil Bahuri attended the National Insight Test which leads to the dismissal of competent senior KPK employees and is currently handling crucial cases. This study attempts to determine how the two major Indonesian media, Republika and Tempo, produce discourse. In this case, it will be examined how Republika and Tempo portray the KPK. A methodological and theoretical approach is used in this study procedure. To see the theoretical analysis of Fairclough's critical discourse, the descriptive analysis methodological technique was adopted. The present discourse is examined via three lenses: (a) textual dimension, (b) discursive dimension, and (c) sociocultural dimension. According to the findings of the research from the three Fairclgh study items, Republika has a negative image of the KPK, whereas Tempo has a positive image of the KPK.